Pronosticos AClimateColombia: A system for the sustainable provision of agro-climatic information for agricultural adaptation in Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The platform is implemented for Colombia, and being used by farmers organizations.